1996
DOI: 10.1007/bf00052945
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of contralateral breast cancer following a first primary breast cancer (Washington, United States)

Abstract: To evaluate predictors of contralateral breast cancer risk, we examined data from a nested case-control study of second primary cancers among a cohort of women in western Washington (United States) diagnosed with breast cancer during 1978 through 1990 and identified through a population-based cancer registry. Cases included all women in the cohort who subsequently developed contralateral breast cancer at least six months after the initial diagnosis, but prior to 1992 (n = 234). Controls were sampled randomly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
45
2
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 30 publications
6
45
2
3
Order By: Relevance
“…The higher proportion of SBBC among lobular and potentially other non-ductal histology types is consistent with evidence from a number of studies (Horn & Thompson, 1988;Cook et al, 1996;Dawson et al, 1998;Chen et al, 1999;Hartman et al, 2007;Verkooijen et al, 2007). The higher proportion for large cancers is supported by previous studies (Verkooijen et al, 2007;Beckmann et al 2011) with one study finding this to have resulted from using size of the more dominant lesion for cases detected at the same time (Beckmann et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…The higher proportion of SBBC among lobular and potentially other non-ductal histology types is consistent with evidence from a number of studies (Horn & Thompson, 1988;Cook et al, 1996;Dawson et al, 1998;Chen et al, 1999;Hartman et al, 2007;Verkooijen et al, 2007). The higher proportion for large cancers is supported by previous studies (Verkooijen et al, 2007;Beckmann et al 2011) with one study finding this to have resulted from using size of the more dominant lesion for cases detected at the same time (Beckmann et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, history of chest-wall radiation for Hodgkin disease of adolescence and early adulthood is well known to result in higher rates of breast carcinomas after an interval of more than 5-10 years. 43 However, more recent studies of bilateral breast carcinoma reported by Cook et al 32 in 1996 and Broët et al 34 in 1995 have shown no association between radiation for treatment of the first breast carcinoma and risk for subsequent contralateral disease. The current study supports this lack of correlation.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the current study was to evaluate risk factors for bilateral disease by using a sample of randomly selected bilateral breast carcinoma patients and comparing them with an age-and stage-matched group of control patients with unilateral disease. One other case-control series 32 relied exclusively on abstractions from the medical records of several different health care institutions in the state of Washington. This method resulted in a large patient population for evaluation (640 patients, including 234 with bilateral disease); however, the histopathology data were limited by not subjecting the study tumors to the scrutiny of a standardized review, a scrutiny that was part of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annual incidence of CBC increases during the follow-up of breast cancer survivors. Common CBC risk factors were confirmed in our population, apart from tumor lobular histology and hormone receptors [18,[27][28][29][30][31]. When considering BMI as an independent risk factor for CBC, CBC events are expected to increase along with improved breast cancer survival [29] and the given worldwide epidemic of overweight and obesity [19].…”
Section: Discussionmentioning
confidence: 79%